Fourth branchial pouch sinus — an unusually late initial presentation - Pal, Indranil (Springer-Verlag, 2009)
OBJECTIVE: Here we present an unusual case of a male patient with 4th branchial pouch sinus with an initial presentation of pseudothyroiditis at an unusually late age of 20 years. METHOD: Case report and a review of the world literature concerning 4th branchial pouch sinus is presented. RESULT: The patient was diagnosed by radiology and endoscopy and treated surgically. Histopathology revealed chronic inflammatory changes, which pointed towards recurrent sub clinical low-grade inflammations over the years keeping the condition occult till 20 years of age. CONCLUSION: According to available literature it almost always presents in the first decade of life when it might be misdiagnosed. However our report shows it may also exist with sub clinical inflammations or infections and present at a much later stage in life, when the possibility of such a sinus shouldn’t be ruled out on the basis of lack of history of recurrent neck inflammations.